Let x = 1 0 1 0 0 , y = 1 0 x , z = 1 0 y and let
a 1 = x ! , a 2 = x y , a 3 = y x , a 4 = z x , a 5 = e x y z , a 6 = z y 1 , a 7 = y x z .
You might want to use the Stirling's approximation of n ! ≈ 2 π n ( n + 2 1 ) e − n for large n .
Arrange a 1 , a 2 , a 3 , a 4 , a 5 , a 6 , a 7 in increasing order and catenate the index number of your sequence as the answer.
For example, if you think a 1 < a 2 < a 3 < a 4 < a 5 < a 6 < a 7 , then input 1 2 3 4 5 6 7 as the answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice usage of f ( x ) . What motivates such an approach?
Nice usage of f ( x ) . What motivates such an approach?
Log in to reply
The huge numbers (incidentally powers of 1 0 ) involved motivates the use of f ( x ) = lo g x to downscale them for easier comparison. However, after applying the logarithm function once, some of the numbers remain exceedingly large, so f ( x ) = lo g ( lo g x ) is chosen. It should be noted that lo g x > 0 for all a i , so f ( x ) is defined. If we choose f ( x ) = lo g ( lo g ( lo g x ) ) , it would not be defined for x = a 6 .
Problem Loading...
Note Loading...
Set Loading...
Define the function f ( x ) = lo g ( lo g ( x ) ) . Since f ( x ) is increasing for x > 1 , we can infer that if f ( x 2 ) > f ( x 1 ) , then x 2 > x 1 .
Now,
f ( x ! ) ≈ lo g ( lo g ( 2 π ( 1 0 1 0 0 ( 1 0 1 0 0 + 2 1 ) e − 1 0 1 0 0 ) )
= lo g ( lo g ( 2 π 1 0 ( 1 0 1 0 2 + 5 0 ) e − 1 0 1 0 0 ) )
= lo g ( lo g 2 π + 1 0 1 0 2 + 5 0 − 1 0 1 0 0 lo g e )
≈ lo g ( 1 0 1 0 2 )
= 1 0 2
Note that 1 0 1 0 2 is larger than 1 0 1 0 0 lo g e by orders of magnitude of at least 2 , so our approximation is justified.
We do the same thing to a 2 , a 3 , a 4 , a 5 , a 6 , a 7 and find that
f ( a 1 ) ≈ 1 0 2
f ( a 2 ) = 1 0 1 0 0 + 2
f ( a 3 ) = 2 0 0
f ( a 4 ) = 1 0 1 0 0 + 1 0 0
f ( a 5 ) = 1 0 0 + 1 0 1 0 0 + 1 0 1 0 1 0 0 + lo g ( lo g e ) ≈ 1 0 0 + 1 0 1 0 0 + 1 0 1 0 1 0 0 . (As an exercise, prove this)
f ( a 6 ) = 0
f ( a 7 ) = 1 0 1 0 1 0 0
All of these are relatively easy to prove. The readers are invited to verify the results.
It is now obvious that f ( a 6 ) < f ( a 1 ) < f ( a 3 ) < f ( a 2 ) < f ( a 4 ) < f ( a 7 ) < f ( a 5 ) , from which the conclusion a 6 < a 1 < a 3 < a 2 < a 4 < a 7 < a 5 follows.
Therefore, the desired answer is 6 1 3 2 4 7 5 .